PENGATURAN TENTANG HAK ASASI MANUSIA BERDASARKAN UNDANG-UNDANG DASAR 1945 SEBELUM DAN SETELAH AMANDEMEN - Haryanto, Tenang; Suhardjana, Johannes; A. Komari, A. Komari; Fauzan, Muhammad; Wardaya, Manunggal Kusuma (Jurnal Dinamika Hukum, 2008)
The end of the government of Orde Baru that tends to be more authoritharian has emerged the transformation almost in all government hierarchy. The most important transformation is in the material contains or substantive of 1945 constitution, whether material that has been erased, revised or new material. Material contain of the 1945 constitution is the result of the amendment such as the Human Right.  The regulation about human right before amendment 1945 constitution regulated as right and duty of the republic citizen in Indonesia that contains the values of human right and regulated in the article 27 to article 34. The regulation of human right after amendment of 1945 constitution regulated in article 28A to 28J.  The regulation about the human right based on the Law Number 39 Year 1999 concerning the Human Right. It explain there is no right in Indonesia that has the absolute power and unlimited. Human Right is not the right that has the absolute characteristic. In the implementation, its limited by the right, morale, security and order of other people. Because of that,  in the human right also known the existence of human right duty. Moreover, the implementation of the human right has been regulated in the 1945 Constitution. Kata Kunci : Hak Asasi manusia, Amandemen UUD 1945